PENGARUH MOTIVASI TERHADAP PENGEMBANGAN KARIR KARYAWAN (Studi Pada PT Bank Papua Cabang Manado Provinsi Sulawesi Utara) - LAPIUS YIKWA; William A. Areros; Wilhelmina Rumawas (Universitas Sam Ratulangi, 2017)
Bank SulutGo is the Regional Bank of North Sulawesi which has a veryinfluential impact on the sustainability of the economy in North Sulawesi especially inthe Government and Institutional or Community institutions of Bank SulutGo’ svision is Tobecome a Professional banking services company and grow in a healthy way;Transformational leadership is the Process by which people engage with others, andcreate relationships that enhance motivation and morality in leaders, and followers. this typeof leader has an interest in the needs and motivation and morality of followers, and tries tohelp followers achieve their best potential.Collection data is done by spreading the research instrument, the questionnaire thatContains questions to measure transformational leadership and employee performance. theCollected Data Is Further Processed By Using Simple Linear Regression Analysis Based onthe formulation of the problem, the purpose of this study is “ to know the effect oftransformational leadership on employee performance on the Bank Sulut Go KawangkoanBranch “Results of data processing show that there is a significant positive effect given byTransformational Leadership on Employee Performance PT. Bank Sulut Go KawangkowanBranch. Thus the higher the Transformational Leadership of PT Bank Sulut GoKawangkowan Branch hence the higher Level of Employee Performance in the company.Statistically Proved that Transformational Leadership Positively influence on EmployeePerformance so that hypothesis accepted.From the results of this study indicates Transformational Leadership is neededsomeone to stimulate employee to work better and make employee as the most valuableasset in the company. For employee, having a leader who is able to transform in leadershipleads employee to be motivated and keans to work well for rhe company’s progress. thisshows the hypothesis of Transformational Leadership on Employee Performance is PositiveKeywords: Transformational Leadership, Employee Performance.